THE INFLUENCE OF ISLAMIC LAW ON INDONESIAN LEGAL POLITICS (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2024)
Studies on the influence of Islamic law in Indonesia can be one basis for muslims to definethe future strategy of the Indonesian nation closer or familiarizing with Islamic law that hasthe effect of legal politic in Indonesia. At least it show sthat the influence of the process ofIslamization of a society is nothing that can be completed immediately, but the center ofattention is focused on the legal position of Islam can influence on legal politic in indonesiawhic his polarized in the establishment of the legal system. Political policy in the law not onlyin legal proceedings that will be and are being enforced but includes also the law that haveoccurred, have practical purposes to allow positive legislation can be better formulated so asto provide guidance not only on legislation but also to the Courts as an organizer or as animplementing decision. -is has been experienced by the people of Indonesia since the eraDutch colonial that changed significantly when the Indonesian republic independent on 17thof August 1945, because they have to adjust in accordance with applicable law and theconstitutional foundation the state ideology of Pancasila and the Constitution of 1945 or alaw that is built upon the activity and creativity based upon ideals that is sourced on thecultural values of the nation which has long since evolved to the present